Pest categorisation of Paracoccus marginatus - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Paracoccus marginatus (Hemiptera: Sternorrhyncha: Pseudococcidae), the papaya scale, for the EU. It is native to Central America and since the 1990s, it has spread rapidly in mainly tropical areas of the Caribbean, islands in the Indian and Pacific Oceans, Africa and southern Asia. Large populations were detected in northern Israel in 2016. It has not been reported within the EU. It is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. It reproduces sexually and there are up to 11 generations per year in India. The estimated minimum, optimum and maximum temperature thresholds for the adult females are 13.9, 28.4 and 32.1°C, respectively. First‐instar nymphs may move to neighbouring plants by crawling, or be passively dispersed by wind, or hitchhiking on clothing, equipment or animals. It is highly polyphagous, feeding on plants in 172 genera and 54 families. It is an important pest of custard apple (Annona spp.), papaya (Carica papaya) and Hibiscus spp. It also feeds on a wide range of plants cultivated in the EU such as eggplant (Solanum melongena), avocado (Persea americana), citrus (Citrus spp.), cotton (Gossypium hirsutum), grapevine (Vitis vinifera), guava (Psidium guajava), mango (Mangifera indica), passionfruit (Passiflora edulis), pomegranate (Punica granatum), pepper (Capsicum annuum) and tomato (Solanum lycopersicum). Plants for planting, fruits, vegetables and cut flowers are the main potential pathways for entry of P. marginatus into the EU. Climatic conditions in the warmest areas of Cyprus, Greece, Italy and Spain, where host plants occur, would likely allow this species to successfully establish and spread. Reductions in yield and quality of some cultivated hosts including Annona spp., Hibiscus spp. and papaya are anticipated if establishment occurs. Phytosanitary measures are available to reduce the likelihood of entry and spread. P. marginatus meets the criteria that are within the remit of EFSA to assess for this species to be regarded as a potential Union quarantine pest.